Educational management and official recognition of higher education studies in Mexico: academic validation, degree awarding, and professional licensing - Villalobos López, José Antonio (2025)
This study aimed to analyze educational management and the official recognition of higher education studies in Mexico, with emphasis on the validity of academic programs, university degree awarding, and the issuance of professional licenses, considering the implications arising from the coexistence of federal and state-level schemes. Methodologically, a qualitative documentary research design was adopted, with an analytical-interpretative orientation and grounded in the hermeneutic-analytical method. The corpus consisted of 42 normative and institutional documents, as well as relevant academic literature published between 2015 and 2024, selected based on criteria of relevance and regulatory validity. The analysis was conducted in four phases: document collection, thematic classification, normative comparison, and interpretative integration through an analytical matrix, complemented by source triangulation to strengthen traceability and analytical consistency. The findings show that the breakdown of national coordination in the issuance of professional licenses since 2018 has generated regulatory confusion, legal gaps, and jurisdictional conflicts between the federal government and several states, directly affecting professional certification processes. In conclusion, a comprehensive legal reform is required to restore system coherence, ensure legal certainty, and strengthen the administrative unity of professional recognition in Mexico.